Resposta ao tratamento de hepatite C com interferon peguilado e ribavirina após transplante de fígado em um centro de referência no nordeste do Brasil - Araujo Filho, Antonio Haroldo de (2014)
Introduction: Liver disease caused by hepatitis C virus is the leading cause of liver transplantation in the United States and Europe. Unfortunately, recurrence of hepatitis C virus is universal, causing major impact in these patients. Treatment of hepatitis C virus in the posttransplant is a challenge due to poor tolerance and low success rate. Objective: To evaluate the response to hepatitisC virustreatment in patients undergoing liver transplantation at the HUWC / UFC. Methods:From May 18th 2002 to December 18th 2011, 601 patients underwent liver transplantation at the HUWC / UFC from which 176 (29,2%) with hepatitis C virus. Forty patients underwent therapy for hepatitis C after liver transplantation and included in the current study. The sustained virologic response (SVR) was determined, as well as factors associated with SVR and patient survival. Results:The mean age of patients was 53,33 years and 32 (80%) were male. The mean donor age was 42,88 years. Twenty-six patients (65%) were infected with genotype 1. Eight patients (20%) were exposed to hepatitis C virus treatment in the pre-transplant period. Twenty-eight (70%)patients completed the treatment protocol, composed of PEG-INF and RBV for 48 weeks. Only 1patient developed cellular rejection during treatment. The SVR rate was 55%, by intention to treat analysis. The recipient age and the exposure to antiviral treatment in the pre-transplant period were associated with SVR factors in multivariate analysis. Patients were followed up for 57 months on average. Eleven patients died during the study. Survival of patients who achieved RVS at 1, 3 and 5 years was 100%, while in those who did not achieved SVR was 100%, 90% and 78% respectively. Conclusion: The SVR rate was 55%.The SVR rate decreased with increasing age of the receptor. Exposure to antiviral treatment in the pre-transplant period had a negative impact on SVR rate. The overall survival of patients who achieved an SVR was similar to patients who have not achieved an SVR.